Ge-doped silica fibre proton beam measurements: thermoluminescence dose-response and glow curve characteristics - Hassan, M. F.; Rahman, W. N. W. A.; Kadir, A. B. A.; Isa, N. M.; Tominaga, T.; Geso, M.; Akasaka, H.; Bradley, D. A.; Noor, N. M. (Universiti Malaysia Perlis, 2019)
Present investigations concern germanium (Ge) doped (2.3 and 6.0 mol%) silica preforms fabricated into cylindrical- and flat-shaped fibre radiation dosimeters. When subjected to 150-MeV proton beam irradiation, the fibres are observed to produce sensitive dose response. The fibres are fabricated via a modified chemical vapour dopant deposition technique and subsequent pulling process. Prior to irradiation, a thermal annealing process was carried out to erase any pre-irradiation signals potentially existing in the samples. For radiation dose in the range from 1 up to 10 Gy, these optical fibres exhibit an excellent linear relationship, offering coefficients of determination (R²) better than 0.99, suggesting reliable calibration and utilisation. The general structure of thermoluminescence (TL) glow curve is presented as a broad peak, differing from that of the phosphor-based TLD-100 dosimeter. The maximum in the TL glow curve peak manifests at a temperature within the readout range 231- to 350 °C. The relatively high glow-peak temperatures allow the fabricated Ge-doped optical fibres to be measured between room- and high-temperature conditions. In terms of shape, the TL glow curve remains unchanged at different irradiation dose within the investigated range of interest (1 to 5 Gy). The TL properties studied herein provide an important advance in understanding the TL mechanism in the fabricated Ge-doped silica fibres, shown to be viable for use in proton beam dosimetry.